Vitrification technique for female germinative tissue cryopreservation and banking - Almodin, Carlos Gilberto (JBRA Assist Reprod, 2020)
OBJECTIVE: To report on a device designed for the vitrification of germinative tissue, and a systematic vitrification/warming protocol. METHODS: We obtained six fragments of cortical germinative tissue from a human ovary. We randomly chose two fragments and sent them to histological analysis. We vitrified four test samples and stored them for one week in liquid nitrogen (LN), and warmed one week later. We sent the vitrified/warmed fragments to the pathology laboratory, where they analyzed them morphologically under an optical microscope (10-40X). They analyzed the nuclear and cytoplasmic characteristics of the follicular cells, luteal layer, and stroma. The primordial and primary follicles in the fresh and vitrified/warmed fragments were counted and compared with the Mann-Whitney test (p<0.05). RESULTS: There were ovarian follicles in different phases of maturation in both fresh and vitrified/warmed fragments, with a predominance of healthy-looking primordial and primary follicles. In the test fragments, the fusocellular architecture supporting the stromal cells exhibited some foci of edema, and were associated with cells with hydropic degeneration, with cytoplasmic fragmentation and eosinophilia. However, there were no signs of tissue necrosis or autolysis. There was no statistically significant difference between the number of follicles found in the control and test tissue fragments (p>0.05). CONCLUSIONS: There were no significant morphological changes between fresh and vitrified/warmed germinative tissue. The vitrification device and protocol tested were effective in the preservation of human follicles, and should be considered for the banking germinative tissue for the restoration of fertility of women who are submitted to life-saving sterilizing treatments.